2011
DOI: 10.1007/s00213-011-2209-4
|View full text |Cite
|
Sign up to set email alerts
|

Infant maternal separation impairs adult cognitive performance in BALB/cJ mice

Abstract: Our findings suggest that IMS induces deficits in adult emotional, episodic, and spatial memory and reversal learning, but does not alter adult emotional behavior or the response to chronic SSRI treatment in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 81 publications
4
57
0
1
Order By: Relevance
“…Efforts have been made to adapt the paradigm to mice given the advances in murine studies since the C57Bl/6 mouse genome has been sequenced and satisfactorily annotated. However, anxiety and stress response in maternal separation in mice has been reported to be increased 28,29 , decreased 30 or unchanged 31 . A more comprehensive study in mice revealed that levels of maternal care (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to adapt the paradigm to mice given the advances in murine studies since the C57Bl/6 mouse genome has been sequenced and satisfactorily annotated. However, anxiety and stress response in maternal separation in mice has been reported to be increased 28,29 , decreased 30 or unchanged 31 . A more comprehensive study in mice revealed that levels of maternal care (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…of MS-reared BALB/c mice (Wang et al, 2011;Wearick-Silva et al, 2016), demonstrating significant memory impairment only in females. The behavioral findings of this study are in accordance with the hypothesis that sex seems to be a key factor in which ELS would affect stress responsivity in rodents Viveros et al, 2009), the detrimental consequences of MS in short-term memory during the late adolescence stage were also characterized by a sex-specific effect.…”
Section: 4cdh Mrna Levels Induced By Ms Exposure Are Related To Rementioning
confidence: 95%
“…For example, it has been shown that the stress associated with neonatal maternal separation induces cognitive dysfunction and impacts on composition of gut microbiota [16], [17], although the effects change with the time and duration of separation [18], [19]. Similarly, mice kept in germ-free conditions, in which development of the hypothalamic-pituitary-adrenal axis is impaired, exhibit deficits in cognitive function [20].…”
Section: Introductionmentioning
confidence: 99%